Data is everybody's business the fundamentals of data monetization - Wixom, Barbara Haley 1969-; Beath, Cynthia Mathis 1944-; Owens, Leslie (Leslie Ann) 1972- (Cambridge, Massachusetts London, England The MIT Press, 2023)
"A guide for business leaders to understand the capabilities and strategies necessary to make money from their data"--
Includes bibliographical references and index.
Keywords: Big data -- Economic aspects; Data mining -- Economic aspects; Electronic data processing -- Economic aspects